Ethyl Benzene Dehydrogenation in the Presence of Carbon Dioxide Over Fe2O3-Cr2O3 Catalyst - AOUISSI, AHMED; ABDULLAH AL-OTHMAN, ZEID; BAYAHIA, HOCEINE (Asian Journal of Chemistry, 2010)
Fe2O3-Cr2O3 was prepared by co-precipitation method, characterized by means of FTIR and X-ray diffraction (XRD) and tested in the dehydrogenation of ethyl benzene in the presence of carbon dioxide. It was found that the main oxide phases forming the catalysts were Fe2O3 and Cr2O3 . The effect of the contact time (W/F) and the reaction temperature on the catalytic activity were investigated. It was noted that the conversion and the yield of products increased with an increase in W/F from 4.06-12.20 g h/mol. Further increase of W/F did not influence the activity. As for the effect of the reaction temperature, it was found that at higher temperatures, a decrease in the activity with time on stream occurred, owing to coke deposit. The selectivity of the reaction products remained constant for temperatures below to 700 ºC. Further increase in the tempe-rature decreased the selectivity of styrene in favour of that of toluene and benzene.